Molecular Imaging of Nonsmall Cell Lung Carcinomas Expressing Active Mutant EGFR Kinase Using PET with [124I]-Morpholino-IPQA. (17th July 2013) - Yeh, Skye Hsin-Hsien; Lin, Chien-Feng; Kong, Fan-Lin; Wang, Hsin-Ell; Hsieh, Ya-Ju; Gelovani, Juri G.; Liu, Ren-Shyan
Abstract : Mutations in the kinase domain of epidermal growth factor receptor (EGFR) have high levels of basal receptor phosphorylation and are associated with clinical responsiveness to Iressa in patients with nonsmall cell lung cancer (NSCLC). This study aimed to assess the feasibility of morpholino-[ 124 I]IPQA derivative as an in vivo PET imaging tool for the expression of different EGFR mutants in NSCLC. In vitro radiotracer accumulation and washout studies demonstrated a rapid accumulation and progressive retention after washout of morpholino-[ 131 I]IPQA derivative in high EGFR-expressing H1299 NSCLC derivative cell lines (L858R and E746-A750 del cell lines), but not in EGFR-transfected H1299 cell line and vector-transfected H1299 cell line. Using the morpholino-[ 124 I]IPQA derivative, we obtained noninvasive microPET images of EGFR activity in L858R and E746-A750 del subcutaneous tumor xenografts, but not in subcutaneous tumor xenografts grown form control cell line. Different EGFR mutant (activity) tumors have a different morpholino-[ ∗ I]IPQA derivative uptake. However, it still needs to modify the structure of IPQA to increase its water solubility and reduce hepatobiliary clearance. Morpholino-[ 124 I]IPQA derivative may be a potential probe for selection of the candidate patients suffering from NSCLC for the small molecule tyrosine kinase inhibitor therapy (e.g., Iressa) in the future.